Odpowiedzi

Najlepsza Odpowiedź!
2009-11-26T16:26:27+01:00
A) (m+n)(m-2)+(m-n)(m+1) = m² - 2m + nm - 2n + m² + m - nm + n =
= 2m² - m - n

b)(3x-2)(3x-2y+1)-4x(2x-3y+1) =
= 9x² - 6xy + 3x - 6x + 4y - 2 - 8x² + 12xy - 4x =
= x² + 6xy - x + 4y - 2

c) 3(m+1)(n-2)+2(n+1)(m-2) = (3m + 3)(n - 2) + (2n + 1)(m - 2) =
= 3mn - 6m + 3n - 6 + 2mn - 4n + m - 2 = 5mn - 5m - n - 8

d) x(x+1)(x+2)-x(x-1)(x-2) = (x² + x)(x+2) - (-x² - x)(x - 2) =
= x³ + 2x² + x² + 2x + x³ + 2x² - x² + 2x = 2x³ + 4x² + 4x
2009-11-26T16:28:50+01:00
(m+n)(m-2)+(m-n)(m+1)=
m²-2m+mn-2n+m²+m-mn-n=2m²-m-3n

(3x-2)(3x-2y+1)-4x(2x-3y+1)=
9x²-6xy+3x-6x+4y-2-8x²+12xy-4x=x²-7x+4y+6xy-2

3(m+1)(n-2)+2(n+1)(m-2)=
3(mn-2m+n-2)+2(mn-2n+m-2)= 3mn-6m+3n-6+2mn-4n+2m-4=5mn-4m-n-10

x(x+1)(x+2)-x(x-1)(x-2)=
x( x²+2x+x+2)-x(x²-2x-x+2)= x³+2x²+x²+2x-x³+2x²+x²-2x=
6x²
2009-11-26T16:29:42+01:00

(m+n)(m-2)+(m-n)(m+1)=m²-2m+mn-2n+m²+m-mn-n=2m²-m-3n

(3x-2)(3x-2y+1)-4x(2x-3y+1)=9x²-6xy+3x-6x+4y-2-8x²+12xy-4x=x²-7x+4y+6xy-2

3(m+1)(n-2)+2(n+1)(m-2)=3(mn-2m+n-2)+2(mn-2n+m-2)= 3mn-6m+3n-6+2mn-4n+2m-4=5mn-4m-n-10

x(x+1)(x+2)-x(x-1)(x-2)=x( x²+2x+x+2)-x(x²-2x-x+2)= x³+2x²+x²+2x-x³+2x²+x²-2x= 6x²